Interaction of low-intensity laserm light with human blood; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 2 - Bukaty V. I.; Pavlova Ya. V.; Sakovich S. I.; Gaskova О. V.; Ustinov G. G. (Mathematics and mechanics. Physics, 2007)
Заглавие с титульного листа